2008
DOI: 10.1002/cncr.23862
|View full text |Cite
|
Sign up to set email alerts
|

Substantial family history of prostate cancer in black men recruited for prostate cancer screening

Abstract: BACKGROUND. Black men are at increased risk for prostate cancer (PCA), particularly with a family history (FH) of the disease. Previous reports have raised concern for suboptimal screening of black men with an FH of PCA. The extent of FH of PCA are reported from a prospective, longitudinal PCA screening program for high‐risk men. METHODS. Black men ages 35 to 69 years are eligible for PCA screening through the Prostate Cancer Risk Assessment Program (PRAP) regardless of FH. Rates of self‐reported FH of PCA, br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 17 publications
(43 reference statements)
0
6
2
Order By: Relevance
“…The attribution of illness often arises when symptoms develop and begin physically restricting everyday life, especially among men (Smith et al, 2005;Mastalski et al, 2008). In our study, with the exception of tiredness, duration of symptoms was not associated with reported attitudes toward CRC screening.…”
Section: Discussioncontrasting
confidence: 56%
“…The attribution of illness often arises when symptoms develop and begin physically restricting everyday life, especially among men (Smith et al, 2005;Mastalski et al, 2008). In our study, with the exception of tiredness, duration of symptoms was not associated with reported attitudes toward CRC screening.…”
Section: Discussioncontrasting
confidence: 56%
“…If so, they should be screened as aggressively as, or more aggressively than, US-born Black men. Other factors such as increased age and a family history of cancer should increase the probability of being screened for cancer since these are wellestablished risk factors for prostate cancer and should raise awareness of the risk of disease [44,80]. The results of this study however, did not provide a clear answer to this question of variation of prostate cancer prevalence and receipt of a PSA exam by birthplace.…”
Section: Immigrants In the Unitedcontrasting
confidence: 54%
“…Generally, risk factors for cancer and more specifically prostate cancer include family history of cancer, age, and Black race [44,54,77,78]. The literature suggests that although the rate of prostate cancer in the US is highest among African-American men, published rates among men living in the Caribbean are even higher [14,32,79].…”
Section: Immigrants In the Unitedmentioning
confidence: 99%
See 1 more Smart Citation
“…Not only a family history of prostate cancer but also breast/ ovarian cancer increase the risk for men in a given familial line. In such case the relative risk is 1.7 and in the case of incidence of PC together with breast or ovarian cancer, the risk is 5.8 but results from other studies differ [14][15][16] . Segregate studies have found a mostly autosomal dominant heredity in patients with sporadic and familial prostate cancer.…”
Section: -45mentioning
confidence: 79%